2006
DOI: 10.1021/ja057097f
|View full text |Cite
|
Sign up to set email alerts
|

Thionitroxides, RSNHO:  The Structure of the SNO Moiety in “S-Nitrosohemoglobin”, A Possible NO Reservoir and Transporter

Abstract: Considerable evidence suggests that the S-nitrosation of cysteine residues, thought to regulate the activities of many proteins, is involved in the uptake and intracellular trafficking of NO. 1 Indeed, to absorb the neutral NO with thiols, a redox reaction is needed to form Snitrosothiols (RSNOs). [1][2][3] A structure of S-nitrosocysteine in hemoglobin proteins was first reported by Arnone and coworkers in 1998. 4a Interestingly, the resulting protein structure obtained under nonbiological conditions (NO pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…Quantum mechanical calculations demonstrate that two energy minima exist for the C-S-N-O dihedral angle, at 0 and 180°, due to delocalization of the N ϭ O electrons over the S-N bond (a phenomenon that may be familiar from the planar peptide bond within the backbone of proteins). This results in a slightly shorter S-N bond and a 12-kcal/mol energy barrier for rotation of the dihedral between 0 and 180° (39). Both conformations of Cys-10 -SNO that we observed in myoglobin closely matched the predicted and observed geometric parameters for S-nitrosothiols.…”
Section: Production and Stability Of S-nitrosylated Blackfin Tunasupporting
confidence: 70%
“…Quantum mechanical calculations demonstrate that two energy minima exist for the C-S-N-O dihedral angle, at 0 and 180°, due to delocalization of the N ϭ O electrons over the S-N bond (a phenomenon that may be familiar from the planar peptide bond within the backbone of proteins). This results in a slightly shorter S-N bond and a 12-kcal/mol energy barrier for rotation of the dihedral between 0 and 180° (39). Both conformations of Cys-10 -SNO that we observed in myoglobin closely matched the predicted and observed geometric parameters for S-nitrosothiols.…”
Section: Production and Stability Of S-nitrosylated Blackfin Tunasupporting
confidence: 70%
“…A clue to the importance of reactant concentrations on this chemistry emerged from EPR studies, which revealed, in the aftermath of mixing very high concentrations of nitrite and deoxyHb, essentially equal subunit populations of nitrosyl heme [␣Fe(II)NO Ϸ ␤Fe(II)NO], whereas spectra obtained under conditions that simulate key aspects of the in vivo situation exhibit substantial ␤Fe(II)NO preference (16). In addition, the importance of duration of reaction on product distribution was recognized: Aging of NO-deoxyHb samples that is incurred over the lengthy course of the nitrite reaction enables competing chemistry, including redistribution of NO from ␤-to ␣-chains, reductive loss of NO to HNO and quenching of radicals in Hb (4,7,(13)(14)(15)34). Because previous work has suggested collectively that the efficacy of transfer of NO groups from heme to ␤Cys-93 (to form a bioactive SNO) might require not only physiological NO͞Hb ratios and HbNO concentrations (Ͻ 1 M) but also preferential processing of NO within the ␤-chain (14-17), the conditions used in prior work were not optimized for the study of SNO formation.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic distribution of protein and low-molecular-weight NO compounds that subserve NO transport and signaling instantiate the variation in both FeNO and SNO reactivities (4,6,13,[16][17][18][19][20][21][22][23][24] (5,6,13,(16)(17)(18)(19)(20)(21)(22)25). Accordingly, bond dissociation energies of RSNO are reported to vary from Ϸ22 to 32 kcal⅐mol Ϫ1 (6, 26), and the dissociation constants of FeNO can vary by a factor of Ͼ10 6 (13, 23, 24), translating to intrinsic FeNO/SNO lifetimes ranging from seconds to years.…”
Section: Red Blood Cell Vasodilation ͉ S-nitrosohemoglobin ͉ S-nitrosmentioning
confidence: 99%
“…Accordingly, bond dissociation energies of RSNO are reported to vary from Ϸ22 to 32 kcal⅐mol Ϫ1 (6, 26), and the dissociation constants of FeNO can vary by a factor of Ͼ10 6 (13, 23, 24), translating to intrinsic FeNO/SNO lifetimes ranging from seconds to years. Environmental factors that have been reported to influence SNO stability and reactivity, directly or through elicited conformational changes in proteins, include pH (low and high) (5,6,20,26), metal ions (Ca, Mg, Cu, and Fe) (6,14,20,27,28), nucleophiles (ascorbate, thiolate, and amine) (6, 13), local hydrophobicity (denaturants) (29), oxidants and reductants (6, 19), proteolytic enzymes (30), alkylators (31), O 2 tension (5, 32), and various intramolecular interactions (H-bonding, S-, N-, O-coordination, and aromatic residue interactions) (6,16,20,22,(33)(34)(35)(36). Many of these factors also affect FeNO stability (17,23,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation